Factorise x3-23x2+142x-120
Answers
Answered by
1086
[tex] x^{3}- x^{2} -22 x^{2} +22x+120x+120
[/tex]
[tex] x^{2} (x-1)-22x(x-1)+120(x-1) [/tex]
![(x-1) ( x^{2} -22x+120) (x-1) ( x^{2} -22x+120)](https://tex.z-dn.net/?f=%28x-1%29+%28+x%5E%7B2%7D+-22x%2B120%29)
![(x-1) ( x^{2} -12x-10x+120) (x-1) ( x^{2} -12x-10x+120)](https://tex.z-dn.net/?f=%28x-1%29+%28+x%5E%7B2%7D+-12x-10x%2B120%29)
![(x-1) (x(x-12)-10(x-12)) (x-1) (x(x-12)-10(x-12))](https://tex.z-dn.net/?f=%28x-1%29+%28x%28x-12%29-10%28x-12%29%29)
![(x-1) (x-10) (x-12) (x-1) (x-10) (x-12)](https://tex.z-dn.net/?f=%28x-1%29+%28x-10%29+%28x-12%29)
[tex] x^{2} (x-1)-22x(x-1)+120(x-1) [/tex]
Answered by
343
x3-23x2+142x-120
by trial and error method let us see if [x-1] is a factor of this polynimial
therefore p[1]= 1³-23×1²+142×1-120
= 1-23+142-120
= 0
so [x-1] is a factor,
now, to divide [x-1] with x3-23x2+142x-120
by doing this we will get x²-22x+120
to find the other factors of x3-23x2+142x-120 we can split the middle term
x3-23x2+142x-120
=x²-12x+[-10x] +120
=x[x-12]-10[x-12]
=[x-10][x-12]
therefore the factors of x3-23x2+142x-120 are:
[x-1][x-10][x-12]
Similar questions